ANALISIS STRUKTUR BATIN PUISI “SENJA DI PELABUHAN KECIL” KARYA CHAIRIL ANWAR - Muhamad Abdul Rohman (IKIP Siliwangi, 2020)
This This research is motivated by researchers' curiosity about the poetry of a Chairil Anwar someone who makes poetry as a vehicle to express the expression of expressionism and realism of a soul of Chairil Anwar. Soul expressions and poetry are two things that are difficult to find correlation. Through this poem